Unearthing the mediating role of political affiliation in tax compliance determinants: new evidence from Ghana - George Nyantakyi; Francis Atta Sarpong; Faustina Asiedu; Deborah Adjei Bimpeh; Jehoshaphat Kwasi Anenyah Ntoso; Linda Ofeibea Nunoo (Cogent Business & Management, 2024)
This study investigates the moderating role of political party affiliation in the relationship between tax knowledge, service quality, and tax compliance. The study gathered data from 450 respondents comprising informal sector traders within the Kejetia market through a structured questionnaire administered by the Ashtown Small Tax Office personnel. The demographic characteristics reveal age, income, and education as key control variables significantly influencing compliance. Using the Partial Least Square Structural Equation Model (PLS-SEM), the study finds a significant and direct positive relationship between tax knowledge and tax compliance. Additionally, service quality positively and significantly affects tax compliance. Meanwhile, the indirect results reveal that political affiliation positively mediates the relationship between tax knowledge and compliance. The same positive mediation effect was realized for the relationship between service quality and tax compliance. Further robustness checks using demographic segmentations reveal a significant positive correlation between young and old tax compliance groups. Also, low-income taxpayer groups exhibit a positive influence on compliance. The educated group has a significant positive effect on tax compliance. The indirect effect of political affiliation is also positively significant for all categories of demographic segmentation. These outcomes highlight the dynamic role of political party affiliation in enhancing national voluntary tax compliance. The study recommends that individual taxpayers perceive tax compliance as a civic duty and not based on partisanship through political party affiliation. However, the government should also ensure equitable distribution of national infrastructure.
Keywords: 650; Political affiliation; tax compliance; service quality; tax knowledge; partisanship